Viabilidade econômica de sistemas de produção de ciclo completo de bovinos de corte - Ávila, Mozer Manetti de (2015)
Currently there is a constant pressure on producers of beef cattle, fruit of the need of the markets, which became increasingly stringent, remunerating better for animals better finished and in earlier ages. To this end, producers end up having to seek the viability of the system through different production alternatives. Therefore, are shown as alternatives productive cycles of one or two years, aiming at reduce the time of finishing of the males or reduction in the age of first pregnancy of the females through the intensification of the production. This study aimed to evaluate the economic viability of four distinct systems of full cycle in beef cattle. The experiment was conducted at Animal Science Department of the Federal University of Santa Maria, from March 2013 to July 2014. Were considered four productive systems: system one year with animals finished on pasture (1P), or finished in feedlot (1C), and systems two years with animals finished in pasture (2P) or finished in feedlot (2C). The zootechnical data were obtained via meta-analysis. The prices of costs and income were obtained from historical data practiced in state of Rio Grande do Sul. The deterministic economic analysis was performed via economic indicators. According to economic indicators, the only system that become feasible at the end of the planning horizon was the system in two years finished in pasture, where others did not report results as feasible investment project. The largest cost centers were depreciation, feeding supply and taxes. The economic indicators presented themselves as attractive alternatives for the measurement of the economic viability of investment projects in beef cattle at short and long term.